Green synthesis of a silver nanoparticle using Moringa oleifera seed and its applications for antimicrobial and sun-light mediated photocatalytic water detoxification. Issue 4 (August 2021) - Mehwish, Hafiza Mahreen; Rajoka, Muhammad Shahid Riaz; Xiong, Yongai; Cai, Huiming; Aadil, Rana Muhammad; Mahmood, Qaisar; He, Zhendan; Zhu, Qinchang
Abstract: Natural water resources are rapidly being polluted because of improper treatment of sewage from industrial facilities; accordingly, there is an urgent need for environmentally friendly methods of treatment for this type of waste. Here, synthesis of cost effective, green silver nanoparticles (AgNPs) using Moringa oleifera seed (MOS) as a reducing/capping agent and their applications in antimicrobial and photocatalytic oxidation for water treatment are reported. The results revealed that the MOS-AgNPs were crystalline and spherical, with an average size of 4.0 nm. The MOS-AgNPs showed excellent antimicrobial activity against Gram positive ( Staphylococcus aureus ; 14.6 mm) and Gram negative ( Escherichia coli ; 30.6 mm, Salmonella enterica typhimurium (29 mm), and Pseudomonas aeruginosa ; 22.8 mm) bacteria. Moreover, the MOS-AgNPs showed remarkable photocatalytic activity toward organic dyes (methylene blue (> 81%), orange red (> 82%), and 4-nitrophenol (> 75%)) under sunlight irradiation. In addition, > 80% of the toxic Pb metal ions were removed from the treated water by MOS-AgNPs. Under similar conditions, the synthesized MOS-AgNPs retained their photocatalytic efficiency after 10 photocatalytic cycles. Overall, these findings indicate that MOS-AgNPs may be a powerful antimicrobial agent against water borne pathogens as well as a promising and economic agent for use in the treatment of waste generated by industrial dyeing processes. Graphical Abstract: ga1 Highlights: Silver nanoparticles (AgNPs) biosynthesized using Moringa oleifera seed (MOS). MOS-AgNPs exhibited excellent antimicrobial activity against pathogenic bacteria. MOS-AgNPs show efficient sun-light mediated photocatalytic degradation of organic dyes. MOS-AgNPs show excellent lead removal potential from polluted water. MOS-AgNPs might be an excellent candidate for water disinfection.